Website Landing Page Design For Chandi's Harvestime For Marketing Development And Promotion Of Culinary Products - Purwandari, Nuraini; Firmansyah, Boy; Kristantini, Rr. Aryanti; Jonathan, Michael (Indonesian Scientific Publication, 2024)
Chandi's Harvestime is a moving Micro , Small and Medium Enterprise in field culinary. The culinary in question is food and drink. Products made​ including kefir milk, mayonnaise risol , fruit salad , various juices, bakery, cakes dry and still lots again. However , Chandi's Harvestime Not yet has social media and a website promote the product. Promotion and sales in a way direct and only through whatsapp. This purpose of research is designing and creating Websites at Chandi's Harvestime for development marketing and promotion product culinary . The landing page will displays products flagship Chandi's Harvestime , as well information about services and contacts required by the candidate consumer . Method used is design thinking which consists of from empathy , definition , ideation , prototype , and testing . The result of research is in the form of a website- based landing page prototype for promotion product Chandi's Harvestime culinary and already done black box testing results conclusion in accordance with need user .